Reclassification of English Learners - James B. Grissom (Arizona State University, 2004)
Ron Unz, originator of Proposition 227, claimed, prior to the passage of Prop. 227, that the five percent annual reclassification rate of English learners to fluent English proficient indicated bilingual education was a failure. Critics of Prop. 227 have countered that the annual reclassification rate has changed little since the passage of Prop. 227, indicating the new legislation had no effect on reclassification rates. Unfortunately, the annual reclassification rate does not provide a clear indicator of how long it takes students to be reclassified after entering the school system. To better estimate reclassification rates for English learners in California, cohorts were created to track the same groups of students over time. Ron Unz also claimed that test scores for immigrant students improved dramatically after the passage of Prop. 227. To evaluate his claim, average test scores were calculated by language fluency. Based on statewide data from three different cohorts tracked across four years, Prop. 227 has had no effect on reclassification rates or test scores.